Mother-to-Children Plasmodium falciparum Asymptomatic Malaria Transmission at Saint Camille Medical Centre in Ouagadougou, Burkina Faso. (23rd November 2014) - Douamba, Zoenabo; Dao, Nangnéré Ginette Laure; Zohoncon, Théodora Mahoukédé; Bisseye, Cyrille; Compaoré, Tegwindé Rebeca; Kafando, Jacques Gilbert; Sombie, Bavouma Charles; Ouermi, Djeneba; Djigma, Florencia W.; Ouedraogo, Paul; Ghilat, Nadine; Pietra, Virginio; et al.
Abstract : Background . Malaria's prevalence during pregnancy varies widely in parts of sub-Saharan Africa, including Burkina Faso. The objective of this study was to evaluate the incidence of mother-to-child malaria transmission during childbirth at St. Camille Medical Centre in the city of Ouagadougou. Methods . Two hundred and thirty-eight (238) women and their newborns were included in the study. Women consenting to participate in this study responded to a questionnaire that identified their demographic characteristics. Asymptomatic malaria infection was assessed by rapid detection test Acon (Acon Malaria Pf, San Diego, USA) and by microscopic examination of Giemsa-stained thick and thin smears from peripheral, placental, and umbilical cord blood. Birth weights were recorded and the biological analyses of mothers and newborns' blood were also performed. Results . The utilization of long-lasting insecticidal nets (LLINs) and intermittent preventive treatment with sulfadoxine-pyrimethamine (SP) were 86.6% and 84.4%, respectively. The parasitic infection rates of 9.5%, 8.9%, and 2.8% were recorded, respectively, for the peripheral, placental, and umbilical cord blood. Placental infection was strongly associated with the presence of parasites in the maternal peripheral blood and a parasite density of >1000 parasites/ µ L. Conclusion . The prevalence of congenital malaria was reduced but was associated with a high rate of mother-to-child malaria transmission.